ДО 100-РІЧЧЯ З ДНЯ НАРОДЖЕННЯ ВИДАТНОГО ЧЛЕНА СФУЛТ МОДЕСТА РІПЕЦЬКОГО - Гриновець, В.; Ріпецька, О.; Денега, І.; Ренка, М. (Українські медичні вісті, 2023)
ДО 100-РІЧЧЯ З ДНЯ НАРОДЖЕННЯ ВИДАТНОГО ЧЛЕНА СФУЛТ МОДЕСТА РІПЕЦЬКОГО